Sistem Informasi Pengolahan Data Nilai Siswa Berbasis Website Pada MTs Mishbahul Falah Batangan - Diah Ayu Ambarsari (Computer Science (CO-SCIENCE), 2021)
Madrasah Tsanawiyah Mishbahul Falah is an educational institution, but in the process of calculating grades it is still classified as manual because technically the subject teacher provides a list of student scores to the principal, then the class teacher copies the student's scores into a report card based on the value data. Assessing that processing is still manual makes the longer work done, the greater the error rate in processing. The purpose of this study is to build applications that can facilitate value processing using the waterfall method. The initial stage in this research is to collect data for analysis, system analysis which will be used includes analysis of hardware, software, users, technology, system design, database, interface, system implementation, and system testing. The results of this study are Web-Based Student Value Data Processing Applications. Applications that are made can store school data, including teachers, classes, subjects, students, academic years, and carry out the assessment process. This application is expected to be able to solve the problems of the teacher or principal in the process of processing student value data.